Yahoo Web Search

  1. Ad
    related to LHS
  1. Sort by

  1. LHS = sec^6x - tan^6x = (sec^2x - tan^2x)*(sec^4x + tan^4x + tan^2xsec^2x) = 1*[(sec^4x + tan^4x - 2tan^2xsec^2x) + (tan^2xsec^2x + 2tan^2xsec^2x)] = [(sec^2x - tan^2x)^2 + (3tan^2xsec^2x)] = 1 + 3tan^2xsec^2x

    1 Answers · Science & Mathematics · 26/11/2011

  2. LHS = sec²(x) - sec²(y) = (1+tan²(x)) - (1+tan²(y)) = 1 + tan²(x) - 1 - tan²(y) = tan²(x) - tan²(y) = RHS

    3 Answers · Science & Mathematics · 22/07/2009

  3. LHS = cot(θ)sec(θ)sin(θ) = cos(θ)/sin(θ) * 1/cos(θ) * sin(θ) = 1 = RHS I hope this helps!

    3 Answers · Science & Mathematics · 19/05/2011

  4. LHS = 1/sec x + sin x/cot x = cos x + sin x tan x = cos x + sin x * sin x / cos x = cos x/cos x * cos x + sin x * sin x / cos x = (cos^2 x + sin^2 x ) / cos x = 1 / cos x = RHS

    3 Answers · Science & Mathematics · 29/01/2011

  5. LHS = (1+cosx)/sinx = [ 1 + (2cos^2(x/2) - 1)]/2sin(x/2)cos(x/2) = 2cos^2(x/2)/2sin(x/2)cos(x/2) = cos(x/2)/cos(x/2) * cos(x/2)/sin(x/2) = 1 * cos(x/2)/sin(x/2) = cot(x/2) = RHS

    2 Answers · Science & Mathematics · 30/11/2016

  6. LHS= tan^2x - sin^2x =(sin^2x / cos^2x) - sin^2x = (sin^2x - sin^2x cos^2x) / cos^2x = sin^2x (1-cos^2x) / cos^2x since sin^2x = 1 - cos^2x = sin^2x (sin^2x) / cos^2x = sin^2x tan^2x = RHS

    2 Answers · Science & Mathematics · 14/11/2013

  7. LHS = cos2x / (1 + sin2x) = (cos^2 x - sin^2 x) / (cos^2 x + sin^2 x + 2sin x cos x) = [(cos...

    2 Answers · Science & Mathematics · 18/12/2010

  8. LHS = cot(x-y) = 1/tan(x-y) = 1/((tan(x) - tan(y))/(1 + tan(x)tan(y))) = (1 + tan(x)tan(y)) / (tan(x) - tan(y)) ------- now divide the numerator and denominator by tan(x)tan(y) = (cot(x)cot(y) + 1) / (cot(y) - cot(x)) = RHS

    7 Answers · Science & Mathematics · 27/10/2008

  9. LHS = 4-1/x, which goes to 4. RHS = 4+3/x, which also goes to 4 Limit of f(x) is trapped between two functions going to 4, so it's limit is 4 also.

    1 Answers · Science & Mathematics · 27/06/2008

  10. LHS: sin x + sin x cot^2 x = sin x + sin x • cos^2 x/sin^2 x = sin x + cos^2 x/sin x = (sin^2 x + cos^2 x)/sin x = 1/sin x = csc x

    2 Answers · Education & Reference · 19/08/2011

  1. Ads
    related to LHS
  1. Try asking your question on Yahoo Answers